PENJUALAN ADAPTIF SEBAGAI PEMEDIASI KINERJA TENAGA PENJUALAN PERUSAHAAN ASURANSI DI JAWA TENGAH - Dwi Suryanto Hidayat; Aprillia Elly Kusumastuti (Tirtayasa Ekonomika, 2019)
MEA is an opportunity and a challenge for the business world, not without its implications for the insurance industry in Indonesia. Another challenge comes from Indonesia's own domestic policy regarding the existence of the Health Social Security Organizing Agency (BPJS) for the enactment of Presidential Regulation No.111 of 2013 which mandates that every company must register its employees with BPJS. This Perpres indirectly shifts the opportunities for cooperation between private insurance companies and their policy holders. So that private insurance must strive to attract and maintain long-term good relations and be able to provide satisfaction to policyholders is to implement a relational marketing strategy that is the key to success in the performance of salespeople.The purpose of this study is to develop concepts and test empirically constants that contribute greatly to the performance of salespeople and strategies that can be used by insurance company management to improve the performance of salespeople. This study examines and analyzes the causal relationships between constructs in the model, namely the construct of customer orientation, competitive intelligence, and on the performance of salespeople with adaptive sales as mediators. The analysis used in this study is Structural Equation Modeling (SEM) using the AMOS version 22.0 for Windows. The number of samples analyzed was 210 respondents, insurance salespeople in Semarang, Solo, Yogyakarta. The results of this study are that customer orientation, competitive intelligence has an effect on sales force performance mediated by adaptive sales. As for the direct influence of customer orientation on sales performance is not significant. Similarly, the direct influence of competitive performance on sales force performance is not significant.